2004
DOI: 10.1097/01.asn.0000146424.91128.2a
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Sit-Down Patient Care Rounds, Attainment of Clinical Performance Targets, Hospitalization, and Mortality in Hemodialysis Patients

Abstract: Abstract. Sit-down patient rounding in hemodialysis units allows providers to focus collectively on each patient's needs and may affect patient outcomes positively. The objective was to examine whether sit-down rounding practices improve patient outcomes in a cohort of 644 adult hemodialysis patients from 75 outpatient dialysis clinics in 17 states throughout the United States who survived at least 6 mo after enrollment (average follow-up, 3.2 yr). Achievement of well-accepted 6-mo clinical performance targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 29 publications
1
27
1
Order By: Relevance
“…Studies should focus on markers that are amenable to intervention, including the type of vascular access 17 and the frequency of sit-down rounds. 10 In addition, the increased use of telemedicine or partnerships between nephrologists and primary care physicians may facilitate closer follow-up of patients with kidney failure who live in remote areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies should focus on markers that are amenable to intervention, including the type of vascular access 17 and the frequency of sit-down rounds. 10 In addition, the increased use of telemedicine or partnerships between nephrologists and primary care physicians may facilitate closer follow-up of patients with kidney failure who live in remote areas.…”
Section: Discussionmentioning
confidence: 99%
“…7 We used ArcGIS software (version 9.1, ESRI) to determine the shortest distance by road between each patient's residence at the time dialysis was started and the practice location of their attending nephrologist. [8][9][10] We also classified residence location into the following regions:…”
Section: Exposuresmentioning
confidence: 99%
“…Previous research has suggested that staffing patterns and multidisciplinary rounds may influence patient survival. 18,19 In our analyses, we adjusted for patientdoctor ratio and the patient-dialysis staff ratio at facilities, but not for the quality of care by nonphysician staff. The quality of contacts between patients and staff may also be more relevant than its quantity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, sit-down rounds are associated with substantially lower hospitalization and mortality rates. 26 Although supportive data are sparse, it seems obvious that factors such as staff numbers, skill sets, and patient contact time would influence outcomes.…”
Section: Patient Educationmentioning
confidence: 99%